Photonic Crystal Palette of Binary Block Copolymer Blends for Full Visible Structural Color Encryption. (15th August 2021) - Eoh, Hongkyu; Jung, Youngdoo; Park, Chanho; Lee, Chang Eun; Park, Tae Hyun; Kang, Han Sol; Jeon, Seungbae; Ryu, Du Yeol; Huh, June; Park, Cheolmin
Abstract: Structural color (SC) arising from a periodically ordered self‐assembled block copolymer (BCP) photonic crystal (PC) is useful for reflective‐mode sensing displays owing to its capability of stimuli‐responsive structure alteration. However, a set of PC inks, each providing a precisely addressable SC in the full visible range, has rarely been demonstrated. Here, a strategy for developing BCP PC inks with tunable structures is presented. This involves solution‐blending of two lamellar‐forming BCPs with different molecular weights. By controlling the mixing ratio of the two BCPs, a thin 1D BCP PC film is developed with alternating in‐plane lamellae whose periodicity varies linearly from ≈46 to ≈91 nm. Subsequent preferential swelling of one‐type lamellae with either solvent or non‐volatile ionic liquid causes the photonic band gap of the films to red‐shift, giving rise to full‐visible‐range SC correlated with the pristine nanostructures of the blended films in both liquid and solid states. The BCP PC palette of solution‐blended binary solutions is conveniently employed in various coating processes, allowing facile development of BCP SC on the targeted surface. Furthermore, full‐color SC paintings are realized with their transparent PC inks, facilitating low‐power pattern encryption. Abstract : A palette of block copolymer (BCP) photonic crystal (PC) inks, enabling convenient modulation of the structural color in the full visible range is developed by solution blending of two different lamellar‐forming BCPs. The binary blend PC inks are applicable to various solution processes, offering efficient reflection‐mode pattern encryption suitable for emerging encryption technology requiring ultra‐thin, mechanically flexible, and thus skin‐patchable performance.